MOTILITY OF FROZEN THAWED SEMEN AFTER THERMAL RESISTANCE TEST - MATHUR, A K; KUMAR, S; PRABHAKAR, J H; MANDAL, D K; INGALE, H R; JAMES, JOSE (The Indian Journal of Animal Reproduction, 2023)
The data used in this study is an outcome of visit of Central Monitoring Unit (CMU) for evaluation of Semen Station of Kerala and Chitely Dairy, Maharashtra. To assess the post-thaw motility of frozen semen, frozen straws were taken out randomly from the stored semen and were thawed at 37° C for 15 seconds and motility was recorded. The same samples were subjected to thermal incubation test in water bath at 37° C and progressive motility (%) was recorded at 30 and 60 minutesafter incubation. It was observed that the mean post-thaw motility in exotic breeds (HF and Jersey) was 52.40 per cent followed by 50.85 per cent in crossbreds (HF,Jersey, and other crosses).The per cent mean value observed in Indigenous breeds (Tharparkar and Gir) was 45.0 per cent and the difference in post thaw motility was non significant (p<0.05) among breed groups. The overall mean post-thaw motility was 51.02 per cent.Further these thawed samples were incubated at 37° C for 60 minutesand there was consistent reduction in the motility at 30 and 60 minutes. This reduction varied from 6.29 per cent(pure exotic) to 11.25 per cent(indigenous) semen after 30 minutes of incubation and the differences were significant (p<0.05) among breed groups. However, at 60 minutes breed difference in the per cent drop of motility on incubation was non-significant. It was observed that there was no significant difference in the post-thaw motility and reduction in motility after incubation of frozen semen among the evaluated semen stations. Among the semen production stations, the average post- thaw motility of frozen semen varied from 52.70 to 49.70 per cent and motility after 60 minutes of incubation varied from 36.62 to 40.63 per cent, respectively. The results indicated that the reported semen stations are following the Minimum Standard Protocol (MSP) for freezing and thawing and maintaining their semen quality as per the standard guidelines of MSP.